IMPLEMENTATION OF INFORMATION AND TECHNOLOGY (IT) BASED LEARNING IN THE MERDEKA LEARNING CURRICULUM AT SD IN THE SAKTI AREA - Abdullah; Akmaluddin; Mayang Sari; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This type of research is descriptive qualitative, namely research that describes a phenomenon that occurs in the educational environment related to the use of Information Technology (IT) and technology in schools Discusses learning programs that apply information and technology (IT)-based learning that offer strategies, methods, and learning models for teachers and students. Scientific learning strategies that apply information technology and technology (IT) can be implemented in schools and developed outside schools or the wider area. As a result, access to educational resources becomes easier for SD students and teachers. In each academic year, SD provides a limited number of classes at each level, with various subjects. A thorough understanding of information and technology (IT) is required to implement curriculum-compatible learning, enabling it to be used to support a wide range of classes and disciplines. In order for information and technology (IT) to support the improvement of human resources in each subject, this study proposes an implementation plan for information and technology (IT)-based learning in the SD Sakti area.